MANAJEMEN PEMBANGUNAN KEPENDUDUKAN: KOREKSI TERHADAP TEORI MALTHUS - LALU MUH. KABUL (GANEC SWARA, 2019)
This study discusses population development management and it related to the correction of Malthus’s theory. The study method used is quantitative. The result of study indicate on the one side the Malthus’s theory is only relevant during before Second World War where according to Malthus that positives checks operate to control the population. On the other side after the Second World War Malthus’s theory is not fit to the field evidence. Therefore, Malthus’s theory is corrected and its correction is not positive checks that must be operated to control population, but development. In line with the reasons, it is needed a population development management, namelyPopulation Development Grand Design